Pastoral counseling in South Africa with special reference to the Zulu - Msomi, Vivian V (Department of Religious Studies, 2024)
The concern of the study lies with contextualisation of pastoral care and counselling in Africa. The study identifies and critically surveys the cross-cultural dynamics for the discipline pastoral care and counselling in a Zulu milieu. This is perceived to be relevant since this discipline, like others within the corpus of theological thought, has emerged within a Western context. The Zulu context has been chosen in order to gain a manageable area of focus. The dissertation presents a regional, geographical, political and social delineation which.in the process, portrays the Zulu identity as that of a group of people within the family of the Nguni people of South-East Africa. To this group of African people came missionaries from Europe and North America with the message of Christianity in the middle of the nineteenth century. These missionaries, unfortunately, came with Western colonists who had their own motives. This association created an ambiguous legacy which is set out at the introduction to this study. Missiological presuppositions which influenced missionary approaches in Zululand are also described. The study points out that missionaries were faced with a second challenge once the community of the first Zulu Christians (Onenhfevu) emerged. The western missionary had to practice seefsorqe (care of souls) in a culturally new and unfamiliar situation. Quite often, it seems, the missionary was overwhelmed with this radically new situation and reacted, in an impulse of cultural shock, with rigid church discipline, as a form of pastoral care. This practice is analysed critically in view of the church life within the context of which pastoral care and counselling will have to develop in South Africa today. Clinical data in the form of verbatim extracts and case studies from pastoral counselling sessions, are critically analysed in the light of a person-centred approach. This research methodology identifies a people with a rich cultural heritage, yet presently living in a situation of two world-views. This context brings out the seriousness of pastoral responsibility in Africa, which pastors and parishioners face. The Zulu did not receive the Gospel as a tabula rasa. They also do not live out their Christianity in a cultural vacuum. The Zulu always appreciate meaning within the parameters of their cultural paradigm. Therefore, the study seeks points of contact that should constantly be considered in any pastoral counselling of the Zulu, where they encounter intra-psychic and/or inter-personal conflict, or even when they need guidance in decision making in the complex modern life. Cultural symbols, concepts of illness and health, religious outlook, Zulu language nuances, proverbs and marriage customs, identified in this research to be central in Zulu traditional context, are proposed to be "bridges" which should not be neglected in an endeavour to develop effective pastoral counselling of the Zulu. The dissertation, therefore, proposes a multi-dimensional and inter-disciplinary approach to pastoral counselling in Zululand. Issues in the training of pastoral counsellors for an African milieu are also identified.